2004
DOI: 10.1097/01.ju.0000139190.77295.cb
|View full text |Cite
|
Sign up to set email alerts
|

Complete Primary Repair of Bladder Exstrophy: Initial Experience With 33 Cases

Abstract: Complete primary repair with penile disassembly provides a good approach to achieve this purpose without the need for bladder neck reconstruction in some cases. Selection of the proper surgical technique together with adjunctive procedures such as osteotomy and a pain-free early postoperative period can maximize the chance of successful exstrophy repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…El-Sherbiny and Hafez suggested resultant hypospadias after detachment of the distal urethral plate from the glans to be the consequence of retraction of the elastic urethral plate. In contrast with this hypothesis, however, Hommuda and Koth [13] reported a hortotopic meatus in all 33 cases undergoing a disassembly technique. The major concern with leaving the urethral plate attached distally is that this might adversely influence the outcomes of the repair increasing the risk of penile curvature and the chance to end up with a short penis.…”
Section: Discussionmentioning
confidence: 78%
“…El-Sherbiny and Hafez suggested resultant hypospadias after detachment of the distal urethral plate from the glans to be the consequence of retraction of the elastic urethral plate. In contrast with this hypothesis, however, Hommuda and Koth [13] reported a hortotopic meatus in all 33 cases undergoing a disassembly technique. The major concern with leaving the urethral plate attached distally is that this might adversely influence the outcomes of the repair increasing the risk of penile curvature and the chance to end up with a short penis.…”
Section: Discussionmentioning
confidence: 78%
“…The results seem to be better in females. Hafez et al [18] achieved a 50% (three of six) continence rate in girls compared with 16% (three of 19) in boys, though the difference was not statistically significant. Caione et al [21] confirmed these findings in their study of 10 females and 18 age-matched males who had undergone a single-stage CPRE-like procedure.…”
Section: Bladder Neck Reconstruction For Nonneurogenic Urinary Incontmentioning
confidence: 87%
“…A continence rate of 24% without further bladder neck procedures was achieved. Hammouda and Kotb [19] reported a 73% (24/33) continence rate in their series, but only 14 of these patients were toilet trained at assessment. Borer et al [20] have cautioned against interpreting dry intervals as predictors of eventual continence.…”
Section: Bladder Neck Reconstruction For Nonneurogenic Urinary Incontmentioning
confidence: 96%
“…Hammouda and Kotb [44] reported results of their initial 33 patients (26 males, 7 females) who underwent complete primary repair using complete penile disassembly for epispadias repair (in boys) and anterior transverse innominate osteotomy (with postoperative spica casts for immobilization) in all cases. After a median follow-up of 42 months, they reported that 24 children (72.7%) had dry intervals of 3 hours or longer, of which 19 (65.5%) had volitional voiding whereas nine patients (27.3%) were still incontinent after toilet training and required further procedures-such as bulking agents, bladder-neck reconstruction, and augmentation cystoplasty-to achieve dryness.…”
Section: Complete Primary Repair Versus Classic Staged Repair: the Comentioning
confidence: 97%